2019
DOI: 10.1039/c9ra07017f
|View full text |Cite
|
Sign up to set email alerts
|

Acetone fractionation: a simple and efficient method to improve the performance of lignin for dye pollutant removal

Abstract: In this work, it was found that the adsorption capacity of lignin to cationic dye (methylene blue, MB) from aqueous solution could be significantly improved by simple acetone fractionation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 48 publications
(48 reference statements)
1
2
0
Order By: Relevance
“…This explanation is consistent with the observed, strong interactions between the low-and high-MW lignin fractions that may be responsible for lignin association. Li et al observed that lignin fractionated by partial dissolution in acetone significantly increased the adsorption capacity toward a cationic dye, methylene blue [75], thus corroborating our findings.…”
Section: Hydroxyl Group Quantitation Using 31 P Nmr Spectroscopysupporting
confidence: 91%
“…This explanation is consistent with the observed, strong interactions between the low-and high-MW lignin fractions that may be responsible for lignin association. Li et al observed that lignin fractionated by partial dissolution in acetone significantly increased the adsorption capacity toward a cationic dye, methylene blue [75], thus corroborating our findings.…”
Section: Hydroxyl Group Quantitation Using 31 P Nmr Spectroscopysupporting
confidence: 91%
“…It is a basic dye, and on dissolution in an aqueous solution, it provides cations (BGD + ). ese adsorbents were also treated with different chemicals separately, such as ethanol, methanol, isopropanol, 0.1 M HCl, and 0.1 M NaOH, and some chelating agents such as urea [30], thiourea [31], EDTA [32], tartaric acid [33,34], citric acid [35][36][37], lactic acid [38], and acetone [39]. Both adsorbents were chemically processed with organic solvents (ethanol, methanol, and isopropanol) for their modifications in glass beakers covered with aluminum sheets for a period of 3 to 4 hours.…”
Section: Selection Of Chemicals For Chemical Processing Ofmentioning
confidence: 99%
“…Acetone has been investigated as a facile solvent to dissolve lignin. The advantages of using this solvent are low cost, biodegradability, minimization of waste, and good adsorption efficiency (Crestini et al, 2017;Li et al, 2019). For example, Sadeghifar et al (2017) fractionated organosolv lignin with acetone in water to obtain relatively homogeneous lignin fractions.…”
Section: Introductionmentioning
confidence: 99%